Ответы и объяснения

2013-01-29T17:05:49+04:00

а)(2х+1)^2=2х+1

2х+1=1

2х=0

х=0

 

б)(у-2)^2-4=0

у^2-4y+4-4=0

y^2-4y=0

y*(y-4)=0

y1=0, y2=4

 

в)(3х-1)^2=2(3х-1)

(3x-1)=2

3x=3

x=1

 

г)9-(2х-3)^2=0 

9-4x^2+12x-9=0

-4x^2+12x=0

x*(12-x)=0

x1=0, x2=12

2013-01-29T17:06:33+04:00

а)2х(2)+4х+1=2х+1

2х(2)+2х=0

2х(х+1)=0

2х=0       х+1=0

х=0          х=-1

б)у(2)-4у+4-4=0

 у(2)-4у=0

у(у-4)=0

у=0        у-4=0

               у=4

в)9х(2)-6х+1=6х-2

9х(2)-12х+3=0 

 Д=36=6(2)

х1=1       х2=1/3

г)9-4х(2)+12х-9=0

-4х(2)+12х=0

-4х(х-3)=0

-4х=0       х-3=0

х1=0        х2=3

везде где (2) это 2 в квадрате 

у него не праельно